Calibrating Radiocarbon Dates with R - Frerebeau, Nicolas; Lebrun, Brice (The programming historian, 2025)
After reviewing the basic principles and challenges of radiocarbon dating, this lesson teaches you how to use the R programming language to calibrate a set of dates, and then explore and present your results.